Plan de mejoramiento en el área de producción para ser implementado en la empresa Creaciones Lulú en la ciudad de Cali (2013)
Currently, the textile sector is presenting great opportunities for small businesses that have relationships with this sector, this is because from 2003 the Ministry of Commerce elects the textile and clothing sector to be developed as a pilot project of several micro found in Colombia, in order to take advantage of geographic location, human talent, and quality of fabrics for the manufacture of different types of clothing, that the motives for making the process of continuous improvement of all related micro apparel subsector. The following research aims to define the improvement plan for micro Creations Lulu, so that the micro probe is achieved in relation to continuous improvement, and succeeded in identifying a model of competence management, which will allow highlevel staff performance according to capabilities they have to develop in the area will be assigned this by developing a survey that measured the tastes, preferences and expectations they have against the micro, both organizational and technical, so be detailed training plans, this will achieve a vision for microenterprise Creations Lulu has projected over the medium to long term, ensuring higher results in the discharge of their duties, and continued the pursuit of strategic objectives. Additionally, we describe the progress; challenges; needs; opportunities; area improvement plan production of micro Creations Lulu and corresponding actions to be implemented will substantially improve their productivity and be competitive according to the tastes and customer needs, and position in the domestic market and external. It also presents the current and old machinery in order to analyze the capacity of microenterprise Creaciones Lulú.